Rights of the child in the Caribbean : questions and answers (UNICEF Christ ChurchBB, 1999)
Answers questions concerning the Convention on the Rights of the Child; the situation of children in Caricom countries related to rights; and, children's rights issues of importance to the Caribbean. Looks also at children's participation.
Additional copy located in the Office of the Secretary-General